Pemanfaatan kulit skrotom sapi sebagai bahan baku industri barang kulit - Lutfi, Muchtar; Widhiati, Widhiati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The aim of the research was to make use of cow scrotum hides to be raw material in leathergood manufacturing. Forty five pieces of scrotum hides were tanned to crust leather using subsequently 6%, 8% and 10% mineral tanning agent; 15%, 20% and 25% vegetable tanning agent; 15%, 20% and 25% synthetic tanning agent. The physical test results indicated that scrotum cow hides were able to be made use as raw material in leathergood manufacturing. The best tensile strength value was achieved by those tanned with mineral tanning agent 10% (175,33 kg/cm2) and the best elongation at break was achieved by those tanned with synthetic tanning agent 15% (41,00%). Where as by using vegetable tanning agent, no single sample fulfilled the requirements of SNI. 06-0253-1989, Quality and Testing method for Glaced Kid Leather. INTISARI Penelitian ini bertujuan untuk memanfaatkan kulit skrotom sapi sebagai bahan baku industri barang kulit. Empat puluh lima buah kulit skrotom sapi disamak menjadi kulit kras dengan bahan penyamak mineral 6%; 8%; 8% dan 10%, penyamak nabati 15%%; 20% dan 25%, penyamak sintetis 15%; 20% dan 25%. Hasil uji fisika menunjukkan bahwa kulit skrotom sapi bisa dimanfaatkan menjadi bahan baku industry barang kulit. Kekuatan tarik terbaik adalah dengan bahan penyamak mineral 10% (175,33 kg/cm3) dan kemuluran yang terbaik adalah dengan bahan penyamak sintetis 15% (41,00%). Sedangkan dengan bahan penyamak nabati tidak ada yang memenuhi persyaratan SNI.06-0253-1989 Kulit Glace Kambing, Mutu dan Cara Uji.